Rendite della storia: luoghi di cultura nella modernizzazione novecentesca (1890-1966) - Filippo Maria Paladini (Laboratoire Italien)
During the first half of the 20th century, cultural institutions in Venice were directly involved in modernizing the city: opposing political and cultural positions often went parallel to reinventing Venice through the restoration of its ancient facade, educational use of the past, political manipulation of history and, at the same time, investments in contemporary art and the development of mass tourism. Further venetian cultural vitality after World War II until 1966 was supported by the recovery of the previous model: investments in tourism and mass culture, but in a new situation of co-existence between traditionalism, avant-garde art and efforts to establish a renewed dialogue between academics and urban society as well as between Venice and the world. However, historical judgment should be expressed in light of the outcome of the latest season and looking at today’s situation, where the touristic colonization of Venice affects city’s cultural institutions too.